A Multimodal Study of Selected Campaign Posters of All Progressives Congress Presidential Candidate in Nigerian 2023 General Elections - Omole, Davidson Monday; Ogoala, Bibian (Universitas Negeri Yogyakarta, 2024)
The relevance of multimodal features of campaign posters in disseminating intended information to the Nigerian electorate during elections is the focus of this research. The study examines six selected political campaign posters of Bola Ahmed Tinubu, the presidential candidate of the All Progressives Congress (APC) in the 2023 General Elections conducted in Nigeria. The posters, technically designed, are analysed with a view to highlighting their visual and linguistic components. The analysis is also intended to determine their effectiveness in persuading the electorate to vote for the candidate. The posters are chosen because they symbolically express the candidate's and his party's identity and ideology. The study adopts the social semiotic theory of Kress and van Leeuwen (2006) to analyse data sourced from Facebook and WhatsApp. The data are synthesised based on insights from the adopted theory. The paper reveals that Bola Ahmed Tinubu can disseminate information and project his political ideology on the minds of the electorate through visual and non-visual messages contained in the posters. The study concludes that the campaign posters of Bola Ahmed Tinubu contributed to influencing the decision of some Nigerian electorate to vote for him in the 2023 General Elections.The study recommends that future researchers can investigate the relevance of campaign posters in disseminating intended messages to the electorate in other elections conducted in Nigeria.